The evolution of American investigative journalism - Aucoin, James, 1952-; ebrary, Inc. (Columbia, Mo. : University of Missouri Press, 2005)
"History of American investigative journalism and the founding of the Investigative Reporters and Editors (IRE). Discusses the murder of investigative reporter Don Bolles and IRE's subsequent controversial Arizona Project. Applies the social-moral development theory of Alasdair MacIntyre to explain how the IRE contributed to the evolution of American investigative journalism"--Provided by publisher.
The tradition of exposure in American journalism -- The reemergence of investigative journalism, 1960-1975 -- Defining the practice, 1960-1975 -- The founding of IRE -- The Arizona project: IRE's unique contribution to American journalism -- IRE and the mainstreaming of investigative journalism -- A social practice.
Includes bibliographical references and index.
Electronic reproduction.
Keywords: Bolles, Don; Investigative Reporters and Editors, Inc; Investigative reporting -- United States; Electronic books